Evaluation of students’ satisfaction on learning calculus using fuzzy conjoint model / Zarith Sofiah Othman, Ahmad Khudzairi Khalid and CT Munnirah Niesha Mohd Shafee and Nor Baiti Tukiman - Othman, Zarith Sofiah; Khalid, Ahmad Khudzairi; Mohd Shafee, CT Munnirah Niesha; Tukiman, Nor Baiti (Universiti Teknologi MARA, Kedah, 2019)
Learning Calculus is one of the challenges that must be faced by engineering students in a university. In this study, students’ satisfaction of using PowerPoint in learning Calculus was evaluated. There are several ways in analyzing effectiveness in learning Calculus. So far, not much attention has been given to analyzing evaluation of students’ satisfaction from the fuzzy theory perspective. This paper employed the Fuzzy Conjoint Model to evaluate student’s satisfaction in learning the topic ‘integration’ using PowerPoint application. The fuzzy conjoint model presents the linguistic terms in five-point Likert scale. In this model, three main attributes of learning were evaluated: anxiety, learning enjoyment and mobility. The sample of the study consisted of undergraduate students randomly selected from computer science and applied sciences program in the Universiti Teknologi MARA (UiTM) Pahang, Malaysia. The results of the study support the use of fuzzy conjoint model in the evaluation of student’s satisfaction in learning Calculus.